Gypenosides ameliorate ductular reaction and liver fibrosis via inhibition of hedgehog signaling - Hu, Yonghong; He, Xiaoli; Zhou, Xiaoxi; Liang, Yue; Fu, Yadong; Zhang, Linzhang; Fang, Jing; Liu, Wei; Chen, Gaofeng; Mu, Yongping; Zhang, Hua; Cai, Hong; et al. (Frontiers in Pharmacology, 2022)
Backgroud&aims: Ductular reaction (DR) is a common pathological change and thought to have a key role in the pathogenesis and progression of liver fibrosis. Our previous study reported Gypenosides (GPs) ameliorated liver fibrosis, however, the anti-fibrotic mechanisms of GPs are still unclear. Methods: Liver fibrosis was induced in rats by carbon tetrachloride combining with 2-acerylaminofluorene (CCl4/2-AAF), and Mdr2 knockout (Mdr2-/-) mice to evaluate the anti-fibrotic role of GPs. In vitro, WB-F344 cells, a hepatic progenitor cells (HPCs) line, with or without Gli1 overexpressing lentiviral vectors, were induced by sodium butyrate (SB) to validate the mechanism of GPs and NPLC0393, the main ingredient of GPs. Results: Both in CCl4/2-AAF-treated rats and Mdr2-/- mice, GPs obviously reduced the deposition of collagen and hydroxyproline content, inhibited the activation of hepatic stellate cells and inflammatory cell infiltration. Notably, GPs reduced the expressions of Epcam, CK19, CK7, Dhh, Smo, Ptch2, Gli1 and Gli2. Furthermore, CK19+ cells co-expressed Gli1, while the number of CK19+/Gli1+ cells was decreased by GPs. In vitro, GPs and NPLC0393 inhibited the differentiation of WB-F344 cells toward a biliary phenotype. Mechanistically, GPs and NPLC0393 protected against DR by inhibiting hedgehog signaling, which was supported by the results that DR, triggered directly by Gli1 overexpressing lentiviral vector was blocked by administration with GPs or NPLC0393. Conclusion: GPs attenuated DR and liver fibrosis by inhibiting hedgehog signaling, which provided more evidences and a novel mechanism of anti-fibrotic effect of GPs.